(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Chronic kidney disease in young patients is an increasingly recognized health problem with unique clinical characteristics and challenges. The disease often develops silently, with minimal or no early symptoms, which delays diagnosis and allows progressive kidney damage. Both genetic and congenital factors, as well as lifestyle-related risks such as hypertension, diabetes, and obesity, contribute to disease development. Early identification, regular monitoring, and targeted interventions are essential for slowing disease progression, preventing complications, and improving long-term outcomes. Multidisciplinary care and patient education play a crucial role in managing the condition effectively. Understanding the clinical features and risk factors in young patients supports better prevention strategies, timely treatment, and improved quality of life.